2014
DOI: 10.3846/1648715x.2014.969793
|View full text |Cite
|
Sign up to set email alerts
|

Does Real Estate Transparency Matter for Foreign Real Estate Investments?

Abstract: The purpose of this paper is to examine the impact of real estate transparency (RET) on foreign real estate investments (FREI). Most of the previous studies have argued that the free flow of information and the fair and consistent application of local property laws could attract greater amounts of FREI. Using observations from 32 countries covering 2004, 2006, 2008 and 2010 and applying fixed-effect and the generalized method of moments (GMM) techniques, our empirical results reveal that RET is not a major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…In this study, interest rate has been used as a proxy for financing or borrowing costs. The empirical evidence in the literature has also suggested that the increase of interest rate will lead to higher borrowing costs, which in turn might hinder foreign investment, although the significant levels vary different studies (He et al, 2009;Rodriguez & Bustillo, 2010;Farzanegan & Fereidouni, 2014;Hui & Chan, 2014). Therefore, this study expects that there is a negative link between financing costs in the host countries and the flow of FDI in real estate.…”
Section: Real Estate Market-specific Factorsmentioning
confidence: 81%
See 4 more Smart Citations
“…In this study, interest rate has been used as a proxy for financing or borrowing costs. The empirical evidence in the literature has also suggested that the increase of interest rate will lead to higher borrowing costs, which in turn might hinder foreign investment, although the significant levels vary different studies (He et al, 2009;Rodriguez & Bustillo, 2010;Farzanegan & Fereidouni, 2014;Hui & Chan, 2014). Therefore, this study expects that there is a negative link between financing costs in the host countries and the flow of FDI in real estate.…”
Section: Real Estate Market-specific Factorsmentioning
confidence: 81%
“…It is hypothesised that GDP has a positive effect on FDIRE in response to large economies commonly have larger investment opportunities; thereby these economies are preferred. This is also known as the market-seeking FDI hypothesis (Buckley et al, 2007;He et al, 2009;Rodriguez & Bustillo, 2010;Farzanegan & Fereidouni, 2014;Hui & Chan, 2014). We therefore conjecture that host countries' GDP has positive impact on China's outward FDIRE.…”
Section: Gravity-related Factorsmentioning
confidence: 82%
See 3 more Smart Citations